Proteomic Analysis of Differently Expressed Proteins in a Mouse Model for Allergic Asthma - Jeong, HoeSu (The Korean Academy of Medical Sciences, 2005)
Allergic asthma is associated with persistent functional and structural changes in the airways and involves many different cell types. Many proteins involved in allergic asthma have been identified individually, but complete protein profiles (proteome) have not yet been reported. Here we have used a differential proteome mapping strategy to identify tissue proteins that are differentially expressed in mice with allergic asthma and in normal mice. Mouse lung tissue proteins were separated using two-dimensional gel electrophoresis over a pH range between 4 and 7, digested, and then analyzed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MS). The proteins were identified using automated MS data acquisition. The resulting data were searched against a protein database using an internal Mascot search routine. This approach identified 15 proteins that were differentially expressed in the lungs of mice with allergic asthma and normal mice. All 15 proteins were identified by MS, and 9 could be linked to asthma-related symptoms, oxidation, or tissue remodeling. Our data suggest that these proteins may prove useful as surrogate biomarkers for quantitatively monitoring disease state progression or response to therapy.